Geophysical methods applied to the active and closed cells of the "La Cortada" landfill (Norte de Santander) (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2018)
This work presents an application of some non-invasive geophysical techniques for the characterization of the regional landfill “La Cortada,” which is located 5 km from the municipality of Pamplona, in the village of La Chichira (Norte de Santander). The geophysical methods applied in this study were Seismic Refraction Tomography (SRT) and Electrical Resistivity Tomography (ERT). From these techniques, it is possible to determine properties such as electrical resistivity and P-wave seismic velocity. The objective of this study was to identify or delineate the geometry of the landfill, specifically the contact zone between the waste materials and fresh rock. Data were acquired for 5 SRT lines and 5 ERT lines in active and closed areas of the landfill. This work covered the stages of design, acquisition, processing, and interpretation of these geophysical data. Through the analysis of the results in this work, anomalies of electrical resistivity were obtained in sectors of the active and closed areas that may be associated with the accumulation of contaminants, and a range of P-wave seismic velocities was also obtained for the solid waste and the fresh rock. Finally, it was confirmed that these techniques are useful in the characterization of this type of deposit, successfully highlighting contrasts between physical properties.